Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13550-020-00663-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological and dosimetric assessment of DNA-intercalated 99mTc-complexes bearing acridine orange derivatives

Abstract: Background Recently, a new family of 99m Tc(I)-tricarbonyl complexes bearing an acridine orange (AO) DNA targeting unit and different linkers between the Auger emitter ( 99m Tc) and the AO moiety was evaluated for Auger therapy. Among them, 99m Tc-C 3 places the corresponding radionuclide at a shortest distance to DNA and produces important double strand breaks (DSB) yields in plasmid DNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…In this study, kinetic modelling has enabled us to determine the duration of time required to incubate with [ 67 Ga]GaCl 3 or [ 111 In]InCl 3 to induce the same amount of plasmid DNA damage as a specific amount of absorbed radiation dose by EBRT (and vice versa). Traditionally, in vitro or preclinical RBE values are based on clonogenic survival data or studies looking at spermatogenesis in mouse testes [ 49 – 51 ]. These values are then used to inform radiation weighting doses, which in turn are applied to calculate the radiation equivalent dose and finally the effective dose.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, kinetic modelling has enabled us to determine the duration of time required to incubate with [ 67 Ga]GaCl 3 or [ 111 In]InCl 3 to induce the same amount of plasmid DNA damage as a specific amount of absorbed radiation dose by EBRT (and vice versa). Traditionally, in vitro or preclinical RBE values are based on clonogenic survival data or studies looking at spermatogenesis in mouse testes [ 49 – 51 ]. These values are then used to inform radiation weighting doses, which in turn are applied to calculate the radiation equivalent dose and finally the effective dose.…”
Section: Discussionmentioning
confidence: 99%
“…Towards this goal, several research groups have studied radiolabeled DNA intercalators to promote accumulation of AE in the cell nucleus in closer proximity with DNA [ 3 ]. For this purpose, we studied 99m Tc(I) tricarbonyl complexes carrying acridine orange (AO) derivatives as DNA intercalating groups [ 5 , 6 , 7 ]. Our results with the 99m Tc(I)-AO complexes have shown that 99m Tc can cause significant radiation-induced DNA damage, both in vitro in plasmid models and in vivo in human prostate cancer PC3 cells [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we studied 99m Tc(I) tricarbonyl complexes carrying acridine orange (AO) derivatives as DNA intercalating groups [ 5 , 6 , 7 ]. Our results with the 99m Tc(I)-AO complexes have shown that 99m Tc can cause significant radiation-induced DNA damage, both in vitro in plasmid models and in vivo in human prostate cancer PC3 cells [ 6 , 7 ]. Noticeably, we have proved that there is a marked dependence of the biological effectiveness of 99m Tc Auger electrons on the 99m Tc-DNA distance, even for a relatively small increase of such distance (e.g., 10.80 Å vs. 12.92 Å), as estimated by molecular modelling simulations of the DNA-intercalated complexes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The design of G4 binders using medical radiometals can be considered an attractive approach to explore this type of DNA-targeted molecules in cancer theranostics. For this purpose, a plethora of radiometals suitable for SPECT is available (e.g., 99m Tc "m" stands for metastable, 67 Ga, 111 In) or PET (e.g., 68 Ga, 89 Zr) imaging and for systemic targeted radionuclide therapy (e.g., 90 Y, 177 Lu, 225 Ac). These nuclear medicine modalities have already made an enormous contribution to the diagnosis and treatment of cancer in the clinical onset, based on the use of appropriate radioactive compounds designated as radiopharmaceuticals.…”
Section: Dna-targeted Radiocomplexesmentioning
confidence: 99%
“…As mentioned above, Paulo et al performed a detailed and multidisciplinary investigation of the radiation-induced effects of 99m Tc-complexes and structurally related 125 I-labelled derivatives, aiming to assess the influence of the distance to DNA and nature of the radionuclide on the DNA damage. This research study included the spectroscopic characterization of DNA interaction, assessment of DNA damage in vitro and in living cells, cellular and nuclear internalization in tumor cells and computational studies [176,177]. Docking simulations revealed that the compounds 118 (I = 125 I, n = 3, Figure 37A) and 124 (M = 99m Tc, n = 1, Figure 37A) place the corresponding radionuclide at relatively similar distances to the axis of the DNA double helix (10.49 and 10.80 Å, respectively).…”
Section: Dna-targeted Radiocomplexesmentioning
confidence: 99%